Chelate‐Thiolate‐Coordinate Ligands Modulating the Configuration and Electrochemical Property of Dinitrosyliron Complexes (DNICs). Issue 45 (25th September 2015) - Yeh, Shih‐Wey; Lin, Chih‐Wei; Liu, Bai‐Heng; Tsou, Chih‐Chin; Tsai, Ming‐Li; Liaw, Wen‐Feng
Abstract: As opposed to the reversible redox reaction (Fe(NO)2 10 reduced‐form DNIC [(NO)2 Fe(S(CH2 )3 S)] 2− (1 )⇌Fe(NO)2 9 oxidized‐form [(NO)2 Fe(S(CH2 )3 S)] − ), the chemical oxidation of the Fe(NO)2 10 DNIC [(NO)2 Fe(S(CH2 )2 S)] 2− (2 ) generates the dinuclear Fe(NO)2 9 –Fe(NO)2 9 complex [(NO)2 Fe(μ‐SC2 H4 S)2 Fe(NO)2 ] 2− (3 ) bridged by two terminal [SC2 H4 S] 2− ligands. On the basis of the Fe K‐edge pre‐edge energy and S K‐edge XAS, the oxidation of complex 1 yielding [(NO)2 Fe(S(CH2 )3 S)] − is predominantly a metal‐based oxidation. The smaller S1‐Fe1‐S2 bond angle of 94.1(1)° observed in complex 1 (S1‐Fe1‐S2 88.6(1)° in complex 2 ), compared to the bigger bond angle of 100.9(1)° in the Fe(NO)2 9 DNIC [(NO)2 Fe(S(CH2 )3 S)] −, may be ascribed to the electron‐rich Fe(NO)2 10 DNIC preferring a restricted bite angle to alleviate the electronic donation of the chelating thiolate to the electron‐rich Fe(NO)2 10 core. The extended transition state and natural orbitals for chemical valence (ETS‐NOCV) analysis on the edt‐/pdt‐chelated Fe(NO)2 9 and Fe(NO)2 10 DNICs demonstrates how two key bonding interactions, that is, a FeS covalent σ bond and thiolate to the Fe d z 2 charge donation, between the chelating thiolate ligand and the Fe(NO)2 9/10 core could be modulated by the backbone lengths of the chelating thiolate ligands to tune the electrochemical redox potential ( E 1/2 =−1.64 V for complex 1 and E 1/2 =−1.33 V for complex 2 ) and to dictate structural rearrangement/chemical transformations (S‐Fe‐S bite angle and monomeric vs. dimeric DNICs). Abstract : Good two NO : The physical properties and the chemical reactivity of the Fe(NO)2 10 DNICs [(NO)2 Fe(S(CH2 ) n S)] 2− ( n =3 (pdt=1, 3‐propanedithiolate); n =2 (edt=1, 2‐ethanedithiolate), see scheme) were demonstrated to be modulated by the backbone lengths of the chelating thiolate ligands. It was shown that the FeS covalent bond and the thiolate to the Fe d z 2 charge donation modulate the reduction potentials and the chemical transformations.